Genes and miRNAs involved in the development of atherosclerosis (Eurasian Journal of Ecology, 2022)
Atherosclerosis is a complex multifactorial disease. miRNAs, single-stranded RNA molecules may play an important role in the regulation genes expression which involved in atherosclerosis. The work studied binding of miRNAs with mRNA of genes responsible for development of human atherosclerosis.  Based on the literature data of PubMed, a database of 14 genes sequences associated with development of atherosclerosis was created. The miRNA binding sites in mRNAs of the studied genes were found using the miRWalk, miRTarBase, TargetScan, miRDB, and MirTarget programs. 94 binding sites of 51 miRNAs were revealed in mRNA of genes responsible for the development of atherosclerosis. Of the studied binding sites, 15 sites are located in CDS, 17 in 5´UTR, and 62 in 3´UTR. It was defined that some mRNAs of genes have several binding sites with miRNAs. Thus, TNFRSF9 has 15, LDLR - 11 binding sites, TGFB1 - 14 binding sites. It was shown that miR-619-5p more frequently than others binds to mRNA of genes responsible for the development of atherosclerosis. miR-619-5p binds to CD36 with a ΔG/ΔGm ratio of 100%, miR-5096 with a ΔG/ΔGm equal to 100% binds to IL18. Among the studied genes, TGFB1 is the most preferred target of miRNA with high values of interaction, indicating the degree of miRNA binding to mRNA. Thus, using miRWalk, miRTarBase, TargetScan, and miRDB programs, it was shown that mRNA of TGFB1 is a target for many miRNAs in CDS, 5'UTR, and 3'UTR regions.Keywords: miRNA, mRNA, binding sites, atherosclerosis, CDS, 5´UTR, 3´UTR, and nucleotide sequences.